Faktor Pendorong Penyalahgunaan Narkotika di Wilayah Hukum Kepolisian Resor Sukoharjo: Kajian Kriminologi - nila sari (Jurnal Hukum Lex Generalis, 2025)
Drug abuse in Sukoharjo Regency has shown a rising trend influenced by increasingly complex structural, social, and individual factors. This study aims to analyze the characteristics and patterns of drug abuse within the jurisdiction of the Sukoharjo Resort Police and identify criminological factors contributing to the rise of drug-related crimes in the region. Field findings and normative analysis indicate that most offenders are individuals in the productive age group, particularly 17–35 years, with commonly abused substances including methamphetamine, synthetic tobacco, and marijuana. Distribution patterns have evolved through digital communication platforms, "drop-point" systems, and inter-regional networks, enhancing the organized nature of these crimes. From a criminological perspective, the increase in drug cases is driven by weak family supervision, peer influence, economic pressures, rapid urbanization, and the weakening of traditional social controls. Industrial environments and high population mobility further facilitate the entry of illicit drug networks.